Egg-shell CuO/CeO2/Al2O3 catalysts for CO preferential oxidation. (14th September 2015) - Mariño, Fernando; Iglesias, Ignacio; Baronetti, Graciela; Alemany, Luis; Laborde, Miguel
Abstract: Catalytic systems based on copper and cerium supported on γ-Al2 O3 have shown to be extremely effective for CO preferential oxidation. In order to selectively oxidize carbon monoxide, it is desired that only CO can access to the active sites. Since the effective diffusion of H2 is higher than that of CO, an egg-shell type distribution is preferred. With the objective of modifying the radial distribution of the active phases in the catalyst particle, the effect of four variables of the impregnation process is analyzed: metal loading, support-solution contact time, impregnation temperature and drying time. Radial profiles of Cu and Ce show that the egg-shell type distribution is favored by low metal loading, short contact and drying times and by high impregnation temperature. The effect of such variables is stronger on copper profile than on cerium profile. Catalytic performance on COPROX was enhanced by egg-shell type distribution. Highlights: Radial distribution of Cu and Ce within the catalytic particle can be optimized. Low Cu loadings and short contact and drying times favor egg-shell type profiles. Egg-shell type distributions enhance CO oxidation selectivity of COPROX catalysts.